2018
DOI: 10.1016/j.actbio.2017.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Determining the effects of PEI adsorption on the permeability of 1,2-dipalmitoylphosphatidylcholine/bis(monoacylglycero)phosphate membranes under osmotic stress

Abstract: In recent decades, researchers have investigated polyamine-based gene delivery systems as useful alternatives to viral gene carriers. One step that is crucial to the performance of polyamine gene carriers such as polyethylenemine (PEI) is escape from late endosomal vesicles during intracellular delivery. However, the ability of polyamine/DNA polyplexes to effectively escape from endosomes is a little-understood part of the gene therapy techniques that use these polyplexes. Here, we performed investigations usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…As endosomal escape efficiencies of delivery systems in general are routinely extraordinarily low (approximately 1%), 61 SEE assays help to elucidate trends and help suggest when modifications to delivery systems would be advantageous. [33][34][35][36] Lipid bilayer leakage assays 61,62 can be used to similarly reveal endosomal escape capabilities and when engineering may be needed but notably, they do not completely mimic biological contexts. 21 This is imperative to note as endosomal escape is truly the bottleneck of delivery, 22 and the lack of easy assays to evaluate structure-activity relationships hinder delivery vehicle optimization and progress.…”
Section: Discussionmentioning
confidence: 99%
“…As endosomal escape efficiencies of delivery systems in general are routinely extraordinarily low (approximately 1%), 61 SEE assays help to elucidate trends and help suggest when modifications to delivery systems would be advantageous. [33][34][35][36] Lipid bilayer leakage assays 61,62 can be used to similarly reveal endosomal escape capabilities and when engineering may be needed but notably, they do not completely mimic biological contexts. 21 This is imperative to note as endosomal escape is truly the bottleneck of delivery, 22 and the lack of easy assays to evaluate structure-activity relationships hinder delivery vehicle optimization and progress.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, a paper was published very recently by Clark et al who studied the interaction of PEI with endosomal lipids under osmotic stress using synthetic monolayers and vesicles. 56 Moreover, it would be fascinating not only to study the intercellular differences in membrane composition, but also intracellular differences such as different membrane composition resulting from different uptake pathways within the same cell type. This information could lead us towards identifying types of endosomes that are less likely to form these leaks, thereby giving proton sponge-based rupture a better chance at success.…”
Section: Endosomal Leakinessmentioning
confidence: 99%
“…A previous report by Iqbal et al [44] suggested that encapsulation of bacteria in the PDA film also inhibited bacterial proliferation and survival. In another study, positively charged polymers, such as PEI, can enhance permeability of negatively charged bacterial outer membranes [45,46]. It is considered that the PEI chemistry on the titanium surfaces alone can also inhibit bacterial activity [47].…”
Section: Discussionmentioning
confidence: 99%